The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1513/annalsats.202008-1076oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Clinical Features and Outcomes in Mechanically Ventilated Patients with COVID-19 and Acute Respiratory Distress Syndrome

Abstract: Rationale: Patients with severe coronavirus disease (COVID-19) meet clinical criteria for the acute respiratory distress syndrome (ARDS), yet early reports suggested they differ physiologically and clinically from patients with non–COVID-19 ARDS, prompting treatment recommendations that deviate from standard evidence-based practices for ARDS. Objectives: To compare respiratory physiology, clinical outcomes, and extrapulmonary clinical features of severe COVID-19 with non–COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 68 publications
8
34
1
Order By: Relevance
“…Although initial studies suggested high mortality rates for COVID-19 ARDS 1 , recent evidence indicates that clinical outcomes of COVID-19 ARDS may be similar to those of ARDS from other etiologies 47 . Since the histology of COVID-19 ARDS is identical to that of ARDS of other etiologies [classic DAD ( Figures 1 A-D, Supplemental Figure S8) 26-28, 48 ], we hypothesized that the state of regeneration observed here is common to fatal early ARDS regardless of etiology.…”
Section: Resultsmentioning
confidence: 99%
“…Although initial studies suggested high mortality rates for COVID-19 ARDS 1 , recent evidence indicates that clinical outcomes of COVID-19 ARDS may be similar to those of ARDS from other etiologies 47 . Since the histology of COVID-19 ARDS is identical to that of ARDS of other etiologies [classic DAD ( Figures 1 A-D, Supplemental Figure S8) 26-28, 48 ], we hypothesized that the state of regeneration observed here is common to fatal early ARDS regardless of etiology.…”
Section: Resultsmentioning
confidence: 99%
“…We found no significant difference in VRs between different ARDS groups: COVID-19 median (3,4). In fact, compared to VR estimates from a large cohort of non-COVID ARDS, nearly all values from our COVID-19 subjects (1.67 [1.49-2.24]) would have fallen within the second and third quartile (1.44-2.13) of a non-COVID ARDS distribution for VR (5).…”
Section: From the Authorsmentioning
confidence: 51%
“…We recognize that our cohort's small sample size limits statistical power to detect significant differences in VRs, if truly present. However, by contextualizing our results with the available comparative reports (3,4) and historic estimates of non-COVID ARDS VRs (5), COVID-19 is more similar than dissimilar from non-COVID ARDS in terms of dead-space ventilation.…”
Section: From the Authorsmentioning
confidence: 83%
“…Although initial studies suggested high mortality rates for COVID-19 ARDS 1 , recent evidence indicates that clinical outcomes of COVID-19 ARDS may be similar to those of ARDS from other etiologies 47 . Since the histology of COVID-19…”
Section: Non-covid-19 Ards Characterized By Accumulation Of Transitional Cells Without Fibrosismentioning
confidence: 99%